2016
DOI: 10.1371/journal.pone.0167119
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Adaptation and Cue Competition during Learning in an Eriksen Flanker Task

Abstract: Two experiments investigated competition between cues that predicted the correct target response to a target stimulus in a response conflict procedure using a flanker task. Subjects received trials with five-character arrays with a central target character and distractor flanker characters that matched (compatible) or did not match (incompatible) the central target. Subjects’ expectancies for compatible and incompatible trials were manipulated by presenting pre-trial cues that signaled the occurrence of compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For instance, in the Eriksen flanker task, when trial N is congruent (i.e., there is compatibility between target and noise features, e.g., >>>>>), this may reinforce the association between noise features and responses, leading to an increased conflict effect to incongruent stimuli on the subsequent trial (i.e., trial N11) as compared to when the target and noise features were incongruent at trial N. A similar effect can be obtained by using external, arbitrary cues that are associated with different probabilities of subsequent congruent and incongruent trials. This conflict adaptation effect was first reported by Gratton, Coles, and Donchin (1992; see also Botvinick, Braver, Barch, Carter, & Cohen, 2001;Ghinescu, Schachtman, Gratton, & Fabiani, 2016;Ghinescu, Schachtman, Stadler, Fabiani, & Gratton, 2010;Von Gunten, Volpert-Esmond, & Bartholow, 2018), and is generally considered as a classic example of a cognitive control phenomenon, in which the attention weights assigned to different stimulus features are dynamically changed depending on their expected utility. Using Miyake and Friedman's terminology, conflict adaptation can be viewed as a shifting phenomenon, since the relationships between specific cues and responses exist in advance of the trial in which the effect is observed.…”
Section: Trial-by-trial Modulation Of Cognitive Controlmentioning
confidence: 59%
“…For instance, in the Eriksen flanker task, when trial N is congruent (i.e., there is compatibility between target and noise features, e.g., >>>>>), this may reinforce the association between noise features and responses, leading to an increased conflict effect to incongruent stimuli on the subsequent trial (i.e., trial N11) as compared to when the target and noise features were incongruent at trial N. A similar effect can be obtained by using external, arbitrary cues that are associated with different probabilities of subsequent congruent and incongruent trials. This conflict adaptation effect was first reported by Gratton, Coles, and Donchin (1992; see also Botvinick, Braver, Barch, Carter, & Cohen, 2001;Ghinescu, Schachtman, Gratton, & Fabiani, 2016;Ghinescu, Schachtman, Stadler, Fabiani, & Gratton, 2010;Von Gunten, Volpert-Esmond, & Bartholow, 2018), and is generally considered as a classic example of a cognitive control phenomenon, in which the attention weights assigned to different stimulus features are dynamically changed depending on their expected utility. Using Miyake and Friedman's terminology, conflict adaptation can be viewed as a shifting phenomenon, since the relationships between specific cues and responses exist in advance of the trial in which the effect is observed.…”
Section: Trial-by-trial Modulation Of Cognitive Controlmentioning
confidence: 59%
“… 4 Previous work (Ghinescu et al, 2016 ) has shown that behavior does not change across experimental blocks in cued-flanker tasks. There was no age-group by experimental block interaction in this study and thus block was not used as a factor in these ANOVAs.…”
mentioning
confidence: 96%
“…A large history of research has confirmed the reliability of overshadowing and blocking across species and types of learning (including invertebrate species, e.g., Acebes et al, 2009, in garden snails; Prados et al, 2013, in planaria). Focusing on human research, overshadowing has been reported in different learning domains, including spatial learning (Buckley et al, 2019, 2021; Chamizo, 2003; Prados, 2011), contingency judgements (Price & Yates, 1993), fear conditioning (Haesen et al, 2017), evaluative conditioning (Kattner & Green, 2015), multisensory recognition test (Stahlman et al, 2018), and cognitive control tasks (Ghinescu et al, 2016).…”
mentioning
confidence: 99%